Altered aggregation properties of mutant γ-crystallins cause inherited cataract - Sandilands, Aileen (Oxford University Press, 2002)
Protein inclusions are associated with a diverse group of human diseases ranging from localized neurological disorders through to systemic non-neuropathic diseases. Here, we present evidence that the formation of intranuclear inclusions is a key event in cataract formation involving altered γ-crystallins that are un likely to adopt their native fold. In three different inherited murine cataracts involving this type of γ-crystallin mutation, large inclusions containing the altered γ-crystallins were found in the nuclei of the primary lens fibre cells. Their formation preceded not only the first gross morphological changes in the lens, but also the first signs of cataract. The inclusions contained filamentous material that could be stained with the amyloid-detecting dye, Congo red. In vitro, recombinant mutant γB-crystallin readily formed amyloid fibrils under physiological buffer conditions, unlike wild-type protein. These data suggest that this type of cataract is caused by a mechanism involving the nuclear targeting and deposition of amyloid-like inclusions. The mutant γ-crystallins initially disrupt nuclear function, but then this progresses to a full cataract phenotype.